2019
DOI: 10.3390/cells8080820
|View full text |Cite
|
Sign up to set email alerts
|

Protective to a T: The Role of T Cells during Zika Virus Infection

Abstract: CD4 and CD8 T cells are an important part of the host’s capacity to defend itself against viral infections. During flavivirus infections, T cells have been implicated in both protective and pathogenic responses. Given the recent emergence of Zika virus (ZIKV) as a prominent global health threat, the question remains as to how T cells contribute to anti-ZIKV immunity. Furthermore, high homology between ZIKV and other, co-circulating flaviviruses opens the possibility of positive or negative effects of cross-rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 66 publications
2
24
0
Order By: Relevance
“…Vaccine-induced T cell responses likely also contribute to protection against transplacental infection, although the required phenotypes and their contributions in different model systems remain to be fully elucidated [ 48 ]. Induction of T cell responses by the chimeric BinJV vaccines also remains to be characterized, although wild-type mice rather than IFNAR −/− mice are being used for these studies, given the roles of type I IFNs in T cell biology [ 12 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vaccine-induced T cell responses likely also contribute to protection against transplacental infection, although the required phenotypes and their contributions in different model systems remain to be fully elucidated [ 48 ]. Induction of T cell responses by the chimeric BinJV vaccines also remains to be characterized, although wild-type mice rather than IFNAR −/− mice are being used for these studies, given the roles of type I IFNs in T cell biology [ 12 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Macaque models have begun to show the importance of innate and adaptive responses in controlling infection, so our goal was to provide an additional descriptive account of immune responses that occur following infection with a Brazilian ZIKV strain. We also asked whether CD8 T cells have a role in controlling infection, owing to the importance of these cells in providing protection in mouse models 4 6 .…”
Section: Discussionmentioning
confidence: 99%
“…The immunology of ZIKV infection has been most extensively studied in mice, and murine studies have shown the critical importance of type-I interferon (IFN) in limiting disease together with the protective roles of humoral and T cell responses 4 7 . A growing body of literature also describes immune responses following ZIKV infection in nonhuman primates (NHPs), which are often used in preclinical vaccine studies 8 given their genetic and immunologic similarities to humans.…”
Section: Introductionmentioning
confidence: 99%
“…The humoral and cellular immune responses influence ZIKV pathogenesis and play key roles in controlling ZIKV replication [45]. In particular, neutralizing antibodies, induced by ZIKV vaccines, may block infection [27,46], while CD4 + and CD8 + T cells secrete IFN-γ, IL2 (Th1), IL-4, and IL-5 (Th2) cytokines to further promote antibody production or directly kill infected cells [47][48][49][50]. CD8 + T cells are critical for protection against ZIKV infection in mice, non-human primates, and humans [45,48,[50][51][52].…”
Section: Discussionmentioning
confidence: 99%